Management and performance of fattening lambs and goat kids in various rearing systems from Swiss dairy farms - Voigt, Hanna; Zanolari, Patrik; Keil, Nina Maria; Lutz, Barbara; Scriba, Madeleine F.; Ruckli, Antonia K. (Frontiers in Veterinary Science, 2025)
Many of the lambs and goat kids born annually on dairy sheep and goat farms are not needed for herd replacement and are slaughtered for meat. The goal of this study was to describe rearing and fattening systems for lambs and goat kids from dairy production in Switzerland and to assess their impact on gamma globulin serum levels, health, average daily weight gain (ADG) and mortality. Data from 543 lambs and 247 goat kids from 22 dairy sheep and 17 dairy goat farms in Switzerland was collected. All animals were examined twice (goat kids) or thrice (lambs) in visits V1, V2 and V3 and followed from birth until slaughter. The main rearing systems identified were mother-bound (MB), temporarily mother-bound (TMB) and artificial (ART) rearing. Gamma globulin serum were on average lower in lambs (estimated mean [lower/upper confidence interval]: 1.0 [0.77/1.14] g/dl) than in goat kids (1.3 [1.14/1.56] g/dl; p = 0.010) and were higher in younger animals than in older ones (p = 0.005). Lambs fed milk feed ad libitum or temporarily ad libitum had higher ADG between V1 and V2 than those fed restrictively (268 [250/285] and 240 [205/274] g/day; p = 0.041). Lambs reared TMB had higher ADG between V2 and V3 than those reared MB and ART. Lambs transferred to a fattening farm before weaning had lower ADG between V1 and V2 than lambs remaining on their birth farm (198 [179/217] vs. 255 [243/267] g/day; p = 0.003) but higher ADG between V2 and V3 (235 [210/259] vs. 210 [193/229] g/day; p = 0.002). Overall mortality was 11.9% in lambs and 6.1% in goat kids. Mortality was higher in lambs that were weaned on fattening farms (18.5%) than in lambs remaining on their farm of origin (10.8%; p < 0.001). In conclusion, satisfactory results in health and performance could be achieved in all observed rearing and fattening systems. This highlights the need to examine other factors of the rearing management more closely to conclude on the impact of the various rearing systems on the welfare of these lambs and goat kids.